Efecto de promotores de rizogénesis comerciales sobre el crecimiento de esquejes terminales de raicilla (Psychotria ipecacuanha (Brot.) Stokes) en Moravia, Cutris, San Carlos, Costa Rica - Castro-Castillo, Ronny Alberto (Instituto Tecnológico de Costa Rica, 2019)
Survival and growth of “raicilla” were evaluated in stem cuttings subjected to seven rhizogenesis promoters (T2: PROROOT®, T3: RADIX® 35, T4: Green Sol 48, T5: Green Sol 70, T6: ROOTING®, T7: Stimulate and T8: Bambucina). Two applications were carried out, the first on the day that the plantation was established under rapid immersion and the second one after the month established using the Drench for all biostimulants except Green Sol 48 and Green Sol 70, the two applications were made in a foliar manner. The application of growth regulators was applied according to the commercial dose. The trial was conducted at the Ipecacuana from a North farm located in “Moravia de Cutris” and the evaluation was carried out from November 2018 to January 2019. The experimental design used was a Randomized Complete Block Design (RCBD) with four repetitions; 1440 commercial seed cuttings were used as experimental material. Each experimental unit was 0.36 m2 and the useful plot was 0.075 m2. Also, an evaluation of the treatments by four producers in the variables of root health, foliage health, root development, foliage and size of the cuttings was carried out. The results indicated that in the variable number of leaves no significant differences are shown between the treatments while for the other variables there were significant effects, where the Bambucina treatment obtained the highest average survival percentage (79,43%), Radix 35 induced a higher in the volume variables of roots (0,27cm3), dry weight of the aerial part (0,65 gr), Stimulate was greater in stem length (4,45 cm), Green Sol 70 was higher in the variables in root length (4,68 cm) and dry root weight (0,06 gr).
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Reguladores de crecimiento; Sanidad vegetal; Plantas medicinales; Cosechas; Siembra; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production